EMPOWERMENT OF WOMEN THROUGH FARMER WOMEN’S GROUPS IN BUKIT BIRU VILLAGE TENGGARONG DISTRICT KUTAI KARTANEGARA (CASE STUDI OF KWT SRIKANDI JAYA) - AJENG RERNO MURDANINGRUM; Mursidah; Midiansyah Effendi; Dina Lesmana (Syarif Hidayatullah State Islamic University Jakarta, 2025)
The agricultural program for to the Srikandi Jaya Women Farmers Group represents a form of women's empowerment aimed at improving skills, creativity and insight to provide opportunities for women to become more empowered. The purpose of this study was to determine the form of empowerment, the level of participation, and the benefits obtained by the Srikandi Jaya Women Farmers Group. The research was conducted in Bukit Biru, Tenggarong District, Kutai Kartanegara Regency. The sampling method used was purposive and conducted by census. Respondents in this study were 29 people, the analytical method used was descriptive qualitative method by measuring theattitude scale, likert by using a scoring. The results showed that the form of empowerment program given to the Srikandi Jaya women's farmer group was the women's farmer group as alearning class, cooperation unit, and production unit. The participation rate of members of the Srikandi Jaya women's farmer group, the monthly routinemeeting indicator was in the high category with an average score of 10.07, the agricultural counseling/meeting indicator was in the high category with an average score of 13.41, the training program indicator was in the high category with a score an average of 15.83. The benefits of the agricultural extension program included increased group income, enhanced roles of women, higher participation levels, and improved knowledge and insight among members.